Efficient conversion of hemicellulose sugars from spent sulfite liquor into optically pure L-lactic acid by Enterococcus mundtii. (August 2021) - Hoheneder, R.; Fitz, E.; Bischof, R.H.; Russmayer, H.; Ferrero, P.; Peacock, S.; Sauer, M.
Graphical abstract: Highlights: Simulated moving bed chromatography for separation of sugars and lignosulfonates. Sugar fraction from spent sulfite liquor as alternative carbon source. Homofermentative conversion of hexose and pentose sugars by E. mundtii. Full microbial sugar conversion into lactic acid without any by-products. Abstract: Spent sulfite liquor (SSL), a waste stream from wood pulp production, has great potential as carbon source for future industrial fermentations. In the present study, SSL was separated into a hemicellulose derived sugar syrup (HDSS) and a lignosulfonic fraction by simulated moving bed chromatography. The recovery of SSL sugars in the HDSS was 89% and the fermentation inhibitors furfural, 5-hydroxymethylfurfural and acetic acid were removed by 98.7%, 60.5% and 75.5%, respectively. The obtained sugars have been converted to L-lactic acid, a building block for bioplastics, by fermentation with the lactic acid bacterium Enterococcus mundtii DSM 4838. Batch fermentations on HDSS produced up to 56.3 g/L L-lactic acid. Simultaneous conversion of pentose and hexose sugars during fed-batch fermentation of wildtype E. mundtii led to 87.9 g/L optically pure (>99%) L-lactic acid, with maximum productivities of 3.25 g/L.h and yields approaching 1.00 g/g during feeding phase from HDSS as carbon source.